„De Stefanuskroon niet Habsburgsch”: Alternatieven voor de oplossing van de Hongaarse ‘koningskwestie’ en de Nederlandse pers, 1919–1921 - Kerepeszki, Róbert (Acta Neerlandica, 2022)
Following the election of Miklós Horthy as Regent and the dethronement of Charles IV, a special public law situation developed in Hungary, during which the state form of the country remained, in fact, but no one had become authorized to occupy the Hungarian royal throne. The fact that a kingdom existed without a monarch in the heart of contemporary Europe served as an almost constant topic for the political and gossip columns of the domestic and international press, and also earned itself a prominent place among the conversation topics in the rather extensive network of European aristocracy. The importance of the Hungarian problem in the post-‘Great War’ period was also indicated by the lively interest taken by the diplomatic corps of some countries of the continent. Of course, many organizations and individuals tried to win their own ideas in the chaotic situation after the Trianon Treaty and get the Hungarian crown for their candidate or for themselves. This study attempts to introduce the Dutch press narratives in connection with the Hungarian ‘royal question’ between 1919 and 1921. During these years because of the fragile post-war Hungarian internal political situation this problem was at its most acute, and when most of the „candidates” and self-candidates for the Hungarian throne emerged. The paper also looks at the background to some of the motivations behind the candidates and how the news was spread in the international press of the time. The issue raised is of particular interest for the Hungarian-Dutch relations for two reasons. On one hand, there was a fundamental mutual sympathy between the two countries during this period. On the other hand, both countries were monarchies at the time, the public perception of a monarchical state about the predicament of another country with a similar form of government can tell us a lot about the public opinion of the time.